2017
DOI: 10.2139/ssrn.3082767
|View full text |Cite
|
Sign up to set email alerts
|

Eurosystem's Asset Purchases and Money Market Rates

Abstract: Some Euro area money market rates have been standing below the deposit facility rate since 2015, which coincided with the start of the Eurosystem's public sector purchase program (PSPP). In this paper, we explore empirically the interactions between the PSPP and short term secured money market rates (repo rates). We document different channels through which asset purchases may affect the various segments of the Euro area repo market. Using proprietary data from the PSPP purchases and transactions made on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Buying assets allows to inject liquidity beyond what banks demand (Bindseil 2014) and would place all banks in a situation where they are always saturated with liquidity. A practical problem is that a large, safe, and liquid asset market needs to be available to the central bank, or else some market functioning issues could arise, as shown by Arrata et al (2017). The controversy that surrounded the assets purchase programs announced by the ECB in September 2014 suggests that holding large amount of assets might not be an option in the long run.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Buying assets allows to inject liquidity beyond what banks demand (Bindseil 2014) and would place all banks in a situation where they are always saturated with liquidity. A practical problem is that a large, safe, and liquid asset market needs to be available to the central bank, or else some market functioning issues could arise, as shown by Arrata et al (2017). The controversy that surrounded the assets purchase programs announced by the ECB in September 2014 suggests that holding large amount of assets might not be an option in the long run.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Therefore, we test this variable as another proxy for counterparty risk, but it is not significant either. End-of-maintenance period, end-of-month and end-of-quarter increase the changes in rates as it has been documented in the literature (Iori, De Masi, Precup, Gabbi, and Galdarelli (2008), Arrata, Nguyen, Rahmouni-Rousseau, and Vari (2017)).…”
Section: Empirical Implicationsmentioning
confidence: 59%
“…In particular, we show that because of the opportunity cost of collateral, interest rates in the secured market can go below the deposit facility rate (DFR) in the market where only banks are present and repo trades are done against general collateral (not "special" securities). The opportunity cost of collateral itself may stem from imperfect competition or "special" repo trades as suggested in the literature (e.g., Arrata, Nguyen, Rahmouni-Rousseau, and Vari (2017), Huh and Infante (2017), Bech and Klee (2011)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial experience from the period of modestly negative policy rates suggested that the transmission to money market rates worked in the same way as at positive rates (Bech and Malkhozov, 2016;DNB, 2015). In the course of 2015, as some money market rates, such as repo rates, have dropped below the ECB deposit rate, the transmission mechanism got more complicated (Arrata et al, 2017). The transmission to the wider economy remains less evident still.…”
Section: Figure 1 Negative Policy Rates In Europementioning
confidence: 99%